The end of the constituent quark model? - Close, F (2004)
In this conference summary talk at Hadron03, questions and challenges for Hadron physics of light flavours are outlined. Precision data and recent discoveries are at last exposing the limitations of the naive constituent quark model and also giving hints as to its extension into a more mature description of hadrons. These notes also pay special attention to the positive strangeness baryon Theta(+)(1540) and include a pedagogic discussion of wavefunctions in the pentaquark picture, their relation with the Skyrme model and related issues of phenomenology.